Las cuerdas magnéticas - Chaves, Max (Universidad de Costa Rica, 2009)
The conception of the magnetic string is presented; it is an infinitely thin bundle of magnetic flux lines. They are surrounded by a film of current that rotates around them, and are a solution of Maxwell’s equations. Their magnetic potentialcontains a line singularity, and its stability can be established topologically. A few comments are added on the possibility that they may exist at a cosmological scale as relics of the Big Bang.